2017
DOI: 10.1021/acs.chemmater.7b00559
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Controlled Electronic Structure and Phase Stability in Thermoelectric Skutterudite CoSb3

Abstract: Abstract:Controlling extrinsic defects to tune the carrier concentration of electrons or holes is a crucial point concerning the engineering application of thermoelectric semiconductors. To understand the defect-controlled electronic structure in thermoelectric materials, we apply density

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…This leads to a much weaker Mg−Si bond in the TBs than that in the Mg 2 Si crystal. The upper half of the nanotwinned Mg 2 Si is the (1-1-1) [1][2][3][4][5][6][7][8][9][10][11][12] slip system, while the lower half is (1-1-1)[-11-2]. Our previous DFT simulations suggested that the (1-1-1)[- slip system is the most likely under pressure [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a much weaker Mg−Si bond in the TBs than that in the Mg 2 Si crystal. The upper half of the nanotwinned Mg 2 Si is the (1-1-1) [1][2][3][4][5][6][7][8][9][10][11][12] slip system, while the lower half is (1-1-1)[-11-2]. Our previous DFT simulations suggested that the (1-1-1)[- slip system is the most likely under pressure [49].…”
Section: Resultsmentioning
confidence: 99%
“…The current strategies for enhancing the zT value are mainly focused either on improving the power factor (S 2 σ) by tailoring the electrical transport properties [6,7] or on reducing κ L through phonon scattering [8][9][10][11]. Due to the strong correlation between S, σ, and κ E , traditional strategy of carrier optimization is often not very effective in improving zT [1,12,13].…”
mentioning
confidence: 99%
“…Relevant reports have investigated an electron count model based on the stability of a wide number of skutterudites, [ 38 ] and the local distortions upon filling and doping, described by a charge compensated compound defect model. [ 39 ] Besides, thermoelectric properties of skutterudites have been investigated by the defect formation effect on [Sb 4 ] rings by electronegative dopants, [ 40 ] the discontinuity of structural parameters at the n/p crossover on increasing filler and Fe content, [ 41 ] the relation of the structural changes with band convergence, [ 42,43 ] and new emergent states [ 44 ] at the conduction band minima. These studies focus on the n‐type behavior by increasing the chemical potential using one type of filler element, while the scope of wider reviews does not include the structural features of filling.…”
Section: Introductionmentioning
confidence: 99%
“…Predictions of carrier concentrations based on the dilute doping assumption are in excellent agreement with experiments, as shown in this work for native BiCuSeO (Section 3.1) and in other studies on Mg 3 Sb 2 , 66 PbTe, 45 KGaSb 4 , 46 and CoSb 3 . 78 In Ref. 11, it is shown that 15 at.…”
Section: P-type Dopantsmentioning
confidence: 99%